Analysis of quality characteristics of formulated low-cost longanisa - Cabral, Robert Gene Liwanag
ABSTRACT Different mungbean preparations (flour, sprouts, and boiled mungbean) were used to partially replace the meat in the production of longanisa. Mungbean sprouts and grains were bought from the market. The former was minced, while the later was in two, half was boiled and mashed, the other half was ground into flour. Each of the three mungbean preparations were combined with riceflour in a 3:7 ratio. The mixtures were used in the product at levels of 30%, 40%, and 50%. Twenty-four consumer panelists evaluated the effects of the type of mungbean preparation used and the extend of substitution on longanisa. Nutritional analysis was performed by proximate analysis to determine moisture content, crude protein, ether extract, crude fiber, ash, and total carbohydrates. The total dietary fiber was determined by using the modified AOAc method. Test results showed that the product preference increased with an increase in meat content in the samples. The nutritional analysis of the three most preferred products (50% Boiled Mongo, 50% Mongo Flour, and 50% Mongo Sprouts) showed that all 3 samples are good sources of essential macronutrients.